2015
DOI: 10.3390/ijms16011677
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Minor Ginsenosides Isolated from the Leaves of Panax ginseng as Inhibitors of Melanogenesis

Abstract: Three minor ginsenosides, namely, ginsenoside Rh6 (1), vina-ginsenoside R4 (2) and vina-ginsenoside R13 (3), were isolated from the leaves of hydroponic Panax ginseng. The chemical structures were determined based on spectroscopic methods, including fast atom bombardment mass spectroscopy (FAB-MS), 1D-nuclear magnetic resonance (NMR), 2D-NMR, and, infrared (IR) spectroscopy. The melanogenic inhibitory activity of compounds 1, 2 and 3 was 23.9%, 27.8% and 35.2%, respectively, at a concentration of 80 µM. Likewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…E (4.2 g). The structures of 1 – 12 were confirmed by comparison of LC/HR‐ESI‐MS data with those of reference ginsenosides identified by our groups in previous publications ( Figures S1 and S2 ) . The analysis was performed by UPLC‐QToF with the binary gradient elution system consisted of 0.1 % formic acid in water (A) and 0.1 % formic acid in acetonitrile (B).…”
Section: Methodssupporting
confidence: 57%
See 1 more Smart Citation
“…E (4.2 g). The structures of 1 – 12 were confirmed by comparison of LC/HR‐ESI‐MS data with those of reference ginsenosides identified by our groups in previous publications ( Figures S1 and S2 ) . The analysis was performed by UPLC‐QToF with the binary gradient elution system consisted of 0.1 % formic acid in water (A) and 0.1 % formic acid in acetonitrile (B).…”
Section: Methodssupporting
confidence: 57%
“…In contrast, current studies of Korean Ginseng (KG) have revealed that the KG could be an useful antimelanogenic cream . Furthermore, the antimelanogenic activity of protopanaxadiol (PPD) and protopanaxatriol (PPT)‐type saponins in Panax species, especially in KG, had been well reported …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it not only is used for its effect on the skin, but is also clearly a scientific approach for the treatment of various diseases [23] , [24] . It has been reported that several ginsenosides and cinnamic acid are inhibitory agents of melanogenesis, and are found mainly in P. ginseng [11] , [25] , [26] . Therefore, we studied the expression of a protein found in melanin synthesis by nontoxic FGA (it has not been studied with respect to the physiological activities, as mentioned in the introduction) in melan-a cells.…”
Section: Resultsmentioning
confidence: 99%
“…Especially, pseudane-VII showed the highest inhibitory activity (42.7%) at a concentration of 8 µg/mL. It has been reported that few active anti-melanogenic agents such as ginsenosides extracted from leaves of Panax ginseng [ 18 ] showed 35.5% inhibitory activity at 80 µM. In addition, cinnamic acid extracted from Cinnamomum cassia Blume and Panax ginseng exhibited 29% inhibitory effect on melanin synthesis at 500 µM [ 19 ].…”
Section: Resultsmentioning
confidence: 99%